PENERAPAN TEKNIK OPTIMASI DALAM MENENTUKAN HARGA KESEPAKATAN GABAH - Mahatma Tuningrat, Ida Ayu (Agrotekno; Vol. 14, No.2 Agustus 2008)
As this far Indonesia which well-known as agrarian country is still undertaking massive import of rice considering the undeniable disaster; therefore, the farmer exchanging value in Indonesia is experiencing a sharp decrease where many farmers gain financial loss. The aim to optimize is to determine the grained-rice price (win-win solution) in which it is the fair solution for both sides by eliminating the price difference that occurs form not linier programme optimizing method by Fibonacci technique. The agreement of grained-rice price on December 2001 (s=1%) is Rp 1540,00/kg ; (s=5%) is Rp 1490,00/kg and on (s=10%) is Rp 1420,00/kg. on January 2002 (s=1%) is Rp 1610,00/kg ; (s=5%) is Rp 1550,00/kg and on (s=10%) is Rp 1480,00/kg; on March 2002 (s=1%) is Rp 1900,00/kg; (s=5%) is Rp 1850,00/kg and on (s=10%) is Rp 1770,00/kg.
Keywords: grained-rice, farmer, rice price